Potensi senyawa antioksidan alami pada berbagai jenis kacang - Margaretha Arinanti (Universitas Respati Yogyakarta, 2018)
The objectives of this research wew to determine antioxidant activity of eight different beans, included snap bean (Phaseolus vulgaris L.), pigeon pea (Cajanus cajan (L.) Millsp.), mung bean (Phaseolus aureus L.) pea bean (Pisum sativum L.) soybean (Glysine max (L.) Merr.), kidney bean (Phaseolus vulgaris L.), yardlong bean (Vigna sinensis var. sesquipedalis L.), and cowpea (Vigna unguiculata L.). Each bean was milled then extracted in 80% ethanol. The extract was evaporated to find antioxidant crude extract. This extract was prepared for antioxidant activity measurement using oth conjugated diene and ferric thiocynate methods. Kidney bean had the highest antioxidant crude extract content followed by yardlong bean. At the concentration of 500 ppm, kidney bean and yardlong bean had the highest antioxidant activity among the beans studied, but lower than tocopherol at the same concentration. The conjugated diene content of both bean was 33% compare to 23% tor tocopherol. Inhibition of linoleic acid oxidation of yardlong bean and kidney bean were 48% and 52% respectively compare to 60% for tocopherol.